Impact of Private Incidence of Corruption and Firm Ownership on Performance of Firms in Central and Eastern Europe - Sandra Blagojevic; Jože P. Damijan (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
The paper investigates how efficiency of business environment and corruption (infirmal payments and state capture) affect the microeconomic perfirmance of firms. The novelty of the paper is to look at these effects in the interaction with the firm ownership. We use firm-level micro data collected by the Business Environment and Enterprise Perfirmance Survey (BEEPS) for 27 transition countries for the period 2002-2009. Among other data, BEEPS collects also infirmation on different corruption activities at the firm-level and firm ownership. We find somehow surprising results that private firms (domestic and foreign owned) are more involved both into infirmal payments as well as state capture activities. Our results also reveal that foreign owned firms that are involved in infirmal payments are likely to benefit from these corruption practices. On the other side, state owned firms are more likely to experience negative effects of involvements in corruption practices on productivity growth. After 2004, involvement of firms in corrupt practices diminished, and that their negative impact on firm perfirmance dissipates indicating an improvement in the stability of business environment and law enforcement.
Keywords: D04; D73; H10; K42; O17; P37; 330; corruption; informal payments; state capture; institutional stability; firm ownership; firm performance